Optimal Fast Integral Decontamination of Bacillus thuringiensis Aerosols and Fast Disinfection of Contaminated Surfaces - José Luis Pérez-Díaz; Tania Martín-Pérez; Cristina del Álamo; Juan Sánchez-García-Casarrubios; José Luis Copa-Patiño; Juan Soliveri; José M. Orellana-Muriana; Jorge Pérez-Serrano; Francisco José Llerena-Aguilar (Microorganisms, 2023)
Aerosolized anthrax (Bacillus anthracis) spores are of extreme health concern and can remain airborne for hours and contaminate all kinds of surfaces, constituting reservoirs from which resuspension is easily produced. The assessment of decontamination techniques must therefore consider both air and surfaces. In the present study, several kinds of disinfecting fogs were experimentally tested against Bacillus thuringiensis spores, which served as a surrogate for Bacillus anthracis, both as aerosols released into the air and spread on porous and non-porous surfaces with different positions and orientations. This technology removed Bacillus thuringiensis spores from the air in 20 min with just a 1 min application of fog. The dynamics and characteristics of the fog, related to aerosol and surface interactions, proved to be critical for optimal performance and decontamination. An optimal configuration could provide effective disinfection even on indirectly reached surfaces. In all cases, 8% hydrogen peroxide (H2O2) provided a higher disinfection rate than 2% glutaraldehyde.